Academic Procrastination in Relation to Achievement Values, Self-esteem, Intelligence and Course Stream : A Multivariate Study - Jadhav, M.G.; Lodhi, P.H.; Khavare, P.B.; Suryawanshi, A.R.; Nandyai, S.L. (INDIAN EDUCATIONAL REVIEW, 2021)
A sample of 451 students, belonging to Arts and Science faculties, from the junior colleges of Maharashtra, were administered to check Academic Procrastination Scale (with four dimensions or ‘sub-scales’), Achievement Values and Anxiety Inventory, Rosenberg’s Self-esteem Scale, and Cattell’s Culture Fair Intelligence Test. The data were analysed by hierarchical MANOVA, multiple regressions and correlations, multivariate multiple regression and canonical correlation analysis. Academic procrastination was negatively related with achievement values, self-esteem and intelligence. Science students procrastinated less than the arts students and this faculty-wise difference was partially accounted by achievement values, self-esteem, and intelligence. Neither gender differences were obtained in academic procrastination nor gender moderated the effect of faculty. The study provided empirical distinction between procrastination in curricular and co-curricular activities. The relationship between academic procrastination and achievement values, self-esteem and intelligence was attributed to procrastination in curricular activities and not procrastination in co-curricular activities. The implications of these findings are briefly indicated in the paper.